(untitled) (Revista de Estudos da Linguagem, 1998)
Abstract Left Deslocation (LD) and Focus (F) are phenomena characterized for putting in relief a constituent of the oral text. In other words, they are focusing strategies frequently used in Brazilian Portuguese (BP).For this reason, I intend to confront them in this paper, in order to check (a) their limits and (b) their structural domains. Thus, my purpose is to answer the following questions: (i) Are these phenomena independent, or do they exert mutual influence in at least some ways? (ii) Is there an obligated superposing between them? (iii) if not, what are the actuation domains (syntactic and/or phonological) of LD and F? (iv) What are the prosodic features of LD and F constituents? (v) What kinds of discursive-pragmatic phenomena motivate LD and F? My main aim is to show that LD shouldn’t be analized as a focus marker in BP, because Focus must be faced as a prosodic category that require a Contrastive Intonation.